2016
DOI: 10.1177/0003319716661446
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Catheter-Directed Thrombolysis in High-Risk and Intermediate-High-Risk Pulmonary Embolism: Results From a Single-Center Cohort

Abstract: We present our single-center results on ultrasound-assisted thrombolysis (USAT) in patients with pulmonary embolism (PE) at intermediate high risk (IHR) and high risk (HR). Our study consisted of 75 patients with PE who underwent USAT (60 at IHR and 15 at HR). The median time delay from symptoms to USAT was 5 days. Ultrasound-assisted thrombolysis resulted in improvements in tricuspid annular plane systolic excursion; pulmonary artery (PA) systolic and mean pressures; Qanadli score; right to left ventricle dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…A higher all-cause mortality was observed in our population compared to other studies [18, 19, 24, 25]. This could, similarly, reflect our study population of high-risk patients only, whose risk of death is almost ten times that of those with intermediate-risk PE [1, 4].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A higher all-cause mortality was observed in our population compared to other studies [18, 19, 24, 25]. This could, similarly, reflect our study population of high-risk patients only, whose risk of death is almost ten times that of those with intermediate-risk PE [1, 4].…”
Section: Discussionsupporting
confidence: 74%
“…Several reasons can be identified for this higher incidence compared to ± 10% major bleeding in previous literature. Our study population involved patients with high-risk PE only, as opposed to 12–22% with high-risk PE in other studies [ 15 , 16 , 18 , 19 , 24 , 25 ]. Furthermore, our findings are based on real-world data and reflect how current guidelines are put into practice.…”
Section: Discussionmentioning
confidence: 99%
“…Experience with other CDT systems in sub-massive or massive PE has been based on off-label utilization in anecdotal case reports, small retrospective series comprising highly selected patient groups, and systematic reviews or meta-analyses of heterogeneous datasets (10)(11)(12)(13). Only one of these, an ultrasound-assisted thrombolysis technology, EkoSonic ® Endovascular System (Boston Scientific Corporation, USA), was tested in randomized clinical trials (7,8,14) and has been reported to facilitate thrombolysis with reduced lytic dosages, which leads to lowered bleeding risk in patients with PE at high and intermediate-high-risk (IHR) status (7,8,(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The results of EKOS in patients with highrisk and intermediate-high-risk PE were analyzed retrospectively in another study including Turkish patients. [26] The authors found that USAT achieved thrombus resolution and hemodynamic healing in both high-risk and intermediate-high-risk PE patients. The complications related to the procedure were acceptable.…”
Section: Discussionmentioning
confidence: 97%